Development of Enterpreneurial-Oriented pada Pondok Pesantren As-Syafiiyah Sidoarjo - Nurul Mujahadah; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2024)
This research aims to develop an entrepreneurial-oriented approach at Pondok Pesantren As-Syafiiyah Sidoarjo. The main problem faced is the lack of understanding and implementation of entrepreneurial concepts in the pesantren environment. The objective of this research is to enhance the understanding and implementation of entrepreneurial principles at Pondok Pesantren As-Syafiiyah. The research method employed is a qualitative approach with data collection techniques including interviews, observations, and document analysis. The main respondents are pesantren administrators, teachers, and students involved in entrepreneurial activities. The collected data are analyzed using an inductive approach to identify key findings. The results show an improvement in the understanding of entrepreneurial concepts among pesantren administrators, teachers, and students. The implementation of entrepreneurial principles has yielded positive impacts, such as increased creativity, innovation, and economic self-reliance within the pesantren community. Although there are still some challenges, concrete steps have been taken to overcome these obstacles.